Działalność lwowskiego koła księży prefektów w II Rzeczypospolitej. „Miesięcznik Katechetyczny i Wychowawczy” 1919–1939 - Kurosz, Jolanta; Jezior, Małgorzata (Studia Pastoralne, 2026)
Priests-Prefects’Association operated in Poland in the years 1919–1939. Their members were priests who were teaching religious education and did the pastoral work in the school environment. Articles presented in Catechetical and Educational Monthly Magazine show the work of priests in the Association. The aim of the activity of the Association was to introduce the idea of the catholic upbringing and to exchange experiences. The Lviv Circle of Priests-Prefects was one of the biggest in the country and the work of the priests was a guiding light for the others. The priests met on weekly meetings where they read their papers out. The main issue of them was their pastoral work at school. In the Circle there were three sections. Their members in detail discussed issues concerning state primary and secondary schools and Marian Sodalities.